A Compact MIMO Ultra-Wide Band Antenna with Low Mutual Coupling - Nguyen, Quoc Dinh; Le, Trong Trung; Le, Dinh Thanh; Tran, Xuan Nam; Yamada, Yoshihide (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a novel compact multipleinput multiple-output (MIMO) antenna with the size of 26 mm × 60 mm × 1.6 mm for ultra-wide band (UWB) applications is proposed. The proposed MIMO antenna consists of two single UWB antennas and a stub placed between the two antennas to reduce the mutual coupling. The proposed antenna achieves the voltage standing wave ratio (VSWR) less than 2 and more than 86% radiation efficiency over the whole band of interest. Performance of the antenna is examined using both simulation and experiment.